Placental Vitamin D-Binding Protein Expression in Human Idiopathic Fetal Growth Restriction - Wookey, Alice F. (J Pregnancy, 2017)
Vitamin D-binding protein is a multifunctional serum protein with multiple actions related to normal health. Vitamin D-binding protein transports vitamin D and influences the metabolism of this key hormone but it also has additional immunomodulatory and actin-clearing properties. We investigated whether vitamin D-binding protein expression is altered in fetal growth restriction-associated placental dysfunction. Protein was extracted from 35 placentae derived from 17 healthy control subjects and 18 gestation-matched subjects with fetal growth restriction (FGR). FGR subjects were further subdivided as idiopathic (n = 9) and nonidiopathic (n = 9). Vitamin D-binding protein and 25(OH) vitamin D were measured by ELISA and normalized to protein concentration. The results showed significantly reduced levels of placental vitamin D-binding protein (control versus FGR, p < 0.05, Student's t-test) that were strongly associated with idiopathic fetal growth restriction (p < 0.01, Kruskal-Wallis), whereas levels of vitamin D-binding protein were not associated with placental 25(OH) vitamin D stores (p = 0.295, Pearson's correlation). As such, vitamin D-binding protein may be a factor in unexplained placental dysfunction associated with idiopathic fetal growth restriction and may potentially serve as a biomarker of this disease.